Media literacy competence and use of new media for civic engagement among Nigerian youths - La'aro, Oba Abdulkadir (2016)
There have been concerns about youths' exposure to risks in the new media environment in Nigeria. Alongside this is also the observation that the youths are not using the new media to engage important issues in society. These raise issues about the media literacy competence of the youths and their civic engagement obligations. Therefore this study investigated media literacy competence among youths and the use of new media in four types of online civic engagement. Cognitive theory of Media Literacy and the Model of Engaged Citizenship served as underpinning theories for the study. The study is a cross sectional survey with systematic sampling of 503 youths in rural and urban areas of Kwara State, Nigeria. Data were analyzed using Partial Least Squares Structural Equation Modeling. The results indicated low level of critical understanding among youths which explains why the youths are exposed to risk in online environment. The study found significant use of new media for civic engagement across new media types. The results did not reveal significant differences in the use of new media for civic engagement on the basis of socio economic and geographical location of the youths. However, it showed that media education significantly moderated the relationship between communication abilities and use of new media for civic engagement. These findings specifically contribute to modeling the relationship between dimensions of media literacy competence and use of new media for civic engagement and the moderating role of media education in the relationship. It confirmed the theoretical notion of the relevance of media literacy to building active and engaged citizenship among the youths. This outcome will guide government policy on the role of media literacy competence in the use of new media such that user maximizes opportunities and minimizes risks in Nigeria's new media environment